Gentrification through the ages: A long-term perspective on urban displacement, social transformation and resistance. Issue 2 (4th May 2022) - Verlaan, Tim; Hochstenbach, Cody
Abstract : Gentrification is one of the most striking urban developments of our time, radically impacting residential, consumption and investment patterns, and urban culture more broadly. Commonly explained as the transformation of working-class or vacant areas of central cities into middle-class and/or commercial areas, it has become a key term in both academic and popular debates. Yet despite its contemporary significance, little is known about gentrification processes predating the repopulation of Western cities from the 1980s onwards. While geographers and urban sociologists are more inclined to focus on recent developments, historians seem wary of using the term when examining the social transformations of bygone eras. Although a limited number of historians have forayed into the field, so far historical approaches have been undeniably scarce. At the same time, the latest gentrification handbook counts up to 500 pages, but only mentions the history of the phenomenon as a backdrop against current events. This historical backdrop is, furthermore, distinctly Anglophone. This leaves us with a remarkable gap in the historical understanding of gentrification, which we believe is attributable to disciplinary boundaries and—from a historical perspective—the relative newness of the term.